Sex differences in cardiovascular physiology and pathophysiology - LaMarca, Babbette; Alexander, Barbara T. (Academic Press, an imprint of Elsevier, 2019)
Sex Differences in Cardiovascular Physiology and Pathophysiology is a comprehensive look into the often overlooked and underappreciated fundamental sex differences between men and women and how those differences affect the cardiovascular system. It covers cardiovascular function, anatomy, cell signaling and the development of pathology. With contributions from world-renowned research investigators, this up-to-date reference compiles critical knowledge on cardiovascular sex differences, providing researchers and clinicians with a better understanding of the diagnosis, prevention and treatment of cardiovascular diseases in both men and women.